Managing Facilities to Ensure Accessibility for Individuals with Disabilities in Higher Education - Ali, Hilmy Farhani; Solihat, Yayu Nuraidah; Nurmalasari, Neneng (IJLHE: International Journal of Language, Humanities, and Education, 2024)
Every individual, including those with disabilities, has the right to equal opportunities in learning, achievement, and personal development. The effectiveness of inclusive education depends on well-managed facilities and infrastructure, as students with disabilities often require customized support. Moreover, specialized tools and applications are vital to addressing their specific needs. This study investigates how facilities and infrastructure are managed to ensure accessibility for individuals with disabilities in higher education. A literature review method was employed, drawing data from sources such as journals and e-books, followed by data collection, classification, and analysis. The results reveal that accessibility for individuals with disabilities in higher education remains insufficient. Many institutions still lack the necessary resources and infrastructure to adequately support students with disabilities